Analysis of lung function tests at a teaching hospital. - Antwi, D.A.; Gbekle, G.E.; Cosmos, H.K.; Ennin, I.E.; Amedonu, E.A.; Antwi-Boasiako, C.; Clottey, M.K.; Adzaku, F.K. (My University, 2011)
To report on the proportions of restrictive, obstructive and combined types of respiratory diseases in patients referred to respiratory units at the Korle Bu Teaching Hospital. This was a retrospective study of lung function test (LFT) data on patients who were referred from clinics both in and outside KBTH. A spirometer was used to assess various lung volume parameters. One quarter of total subjects (25.5%) had obstructive, 14.8% restrictive and 11.7% exhibited combined forms of respiratory disease. The rest showed none of the above conditions and were classified as normal. We also found differences in proportions of the disorders for subjects in different age and weight categories. Whereas obstructive respiratory disease occurred more in obese patients, and patients who were 35 years and above, restrictive and combined respiratory diseases occurred more in underweight patients, and patients below age 35 years. The respiratory diseases suggested in our study were found not to be sex-dependent. Our study indicates that obstructive lung disease was the most predominant respiratory lung ailment among patients referred to the respiratory units of Korle Bu Teaching Hospital.
Keywords: EMTREE medical terms: adolescent; adult; age; aged; article; child; chronic obstructive lung disease; female; Ghana; hospitalization; human; lung disease; lung function test; male; middle aged; obesity; prevalence; retrospective study; statistical model; teaching hospital; MeSH: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Child; Female; Ghana; Hospitalization; Hospitals, Teaching; Humans; Logistic Models; Lung Diseases; Lung Diseases, Obstructive; Male; Middle Aged; Obesity; Prevalence; Respiratory Function Tests; Retrospective Studies; Young Adult